Detection of Interphase Fault Zone in Overhead Power Distribution Networks - E. V. Kalentionok (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
Parametric methods have been recommended on the basis of current and voltage value recording in normal and emergency modes at a sub-transmission substation in order to detect two- and three-phase short circuits in overhead power distribution networks. The paper proposes to detect an inspection zone in order to locate an interphase fault with the help of analytical calculation of distance up to the fault point using 3–4 expressions on the basis of data obtained as a result of multiple metering pertaining to emergency mode parameters  with their subsequent statistical processing.